Hamburg–Saint Petersburg, Sanit Petersburg–Nice: Scenarios for the stability of twinning under stress - Vlaemnick, Erik; Pustoshinskaya, Olga (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2021)
Against the background of the global COVID-19 pandemic and ongoing geopolitical tensions between the Russian Federation and the West, this chapter engages with the dynamics of European-Russia city diplomacy in times of crisis. By means of two representative case studies of existing twinning cities, namely Hamburg–Saint Petersburg on the one hand, and Nice–Saint Petersburg on the other, this chapter explores the evolution of twinning relations during the politically sensitive times. While paying attention to the legal bases and the historic evolution of selected cases of city cooperation, the authors identify major tendencies as well as opportunities in the field of city twinning and engage with the so-called digital turn in city diplomacy which has manifested itself since the start of the global health crisis in early 2020.

Na tle globalnej pandemii COVID-19 i trwających napięć geopolitycznych między Federacją Rosyjską a Zachodem, niniejszy tekst zajmuje się dynamiką europejsko-rosyjskiej dyplomacji miast w czasach kryzysu. Na podstawie dwóch reprezentatywnych studiów przypadków istniejących miast partnerskich, a mianowicie Hamburg–Sankt Petersburg z jednej strony oraz Nicea–Sankt Petersburg z drugiej, rozdział ten bada ewolucję relacji partnerskich w politycznie wrażliwych czasach. Zwracając uwagę na podstawy prawne i historyczną ewolucję wybranych przypadków współpracy miast, autorzy identyfikują główne tendencje, jak również możliwości w dziedzinie partnerstwa miast i angażują się w tak zwany zwrot cyfrowy w dyplomacji miejskiej, który przejawia się od początku globalnego kryzysu zdrowotnego na początku 2020 roku.
Hamburg–Sankt Petersburg, Sankt Petersburg–Nicea. Scenariusze stabilności połączeń bliźniaczych pod wpływem naprężeń
Keywords: twin cities; Saint Petersburg; Hamburg; Nice; stability of city diplomacy; miasta bliźniacze; Sankt Petersburg; Hamburg; Nicea; stabilność dyplomacji miejskiej